FISHERMAN'S RESPONSE TO FISHING EQUIPMENT ASSISTANCE PROGRAM BY LOCAL GOVERNMENT IN LASITAE VILLAGE, TANETE SUB-DISTRICT, RILAU, BARRU DISTRICT - Amriana, Herlina; Pratiwi, Dian; Rais, Rahmi (Meraja journal, 2022)
[Full Paper] to pdf Copyright (c) 2022 Meraja journal